Choosing between Alternative Motor Insurance Policies: A Discrete Choice Experiment - Charles Kwofie; Dieu Donne Yormekpe; Samuel Osei Mensah; Priscilla Botchway (International Journal of Mathematics and Mathematical Sciences)
The research expounds the use of Discrete Choice Experiment (DCE) approach and Random Utility Theory (RUT) in analyzing alternative motor insurance policy choice behaviour for drivers in Sunyani municipality in Brong-Ahafo, Ghana. We design a DCE to identify the factors (premium cost, claims settlement, customer satisfaction, and proximity) that influences an individual choice for insuring with a particular insurance company given the existence of an alternative. Probit model was used in estimating the parameters of the consideration sets of the DCE. The research sampled 100 respondents comprising mainly of private and commercial drivers. The magnitude of estimates from both probit model and estimated marginal effects indicates respondents highly value insurers with the attribute of paying claims promptly, charging moderate premium, and closer in terms of proximity. However, customer satisfaction will result in a disutility of choice of insurer. Also, the levels of customer satisfaction can be traded off for other attributes.